Learning Strategies For Translating English Texts Into Indonesian Students - Br. Kembaren, Farida Repelitawaty; Yusriani; Masriyanti Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Multilingual ability is one of the abilities that is really needed in the global era and industrial era 4.0. One of the most vital international languages ​​is English, because English can connect society with the world in various fields, including education. The method used in this research uses Systematic Literature Review (SLR) to find out the most appropriate method for designing Enterprise architecture in government agencies. This research results in the fact that students are quite familiar with mathematics vocabulary and mathematics learning in English, thus the